Forecasting the yield curve in a data-rich environment: a no-arbitrage factor-augmented VAR approach - Emanuel Mönch (European Central Bank (ECB), 2005)
This paper suggests a term structure model which parsimoniously exploits a broad macroeconomic information set. The model does not incorporate latent yield curve factors, but instead uses the common components of a large number of macroeconomic variables and the short rate as explanatory factors. Precisely, an affine term structure model with parameter restrictions implied by no-arbitrage is added to a Factor-Augmented Vector Autoregression (FAVAR). The model is found to strongly outperform different benchmark models in out-of-sample yield forecasts, reducing root mean squared forecast errors relative to the random walk up to 50% for short and around 20% for long maturities.
Keywords: C13; C32; E43; E44; E52; 330; Affine term structure models; Dynamic Factor Models; FAVAR; yield curve; Zinsstruktur; Rendite; VAR-Modell; Theorie; USA